Gender and age impact on plantar pressure distribution in early adolescence - İlkşan Demirbüken; Bahar Özgül; Eren Timurtaş; Saadet Ufuk Yurdalan; Murat Dinçer Çekin; Mine Gülden Polat (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of the study was to investigate gender and age effect on dynamic plantar pressure distribution in early adolescence. Methods: A total of 524 adolescents (211 women and 313 men; mean age: 12.58 ± 1.11 years (range: 11–14 years)) participated in pedobarographic measurements during gait at self-selected speed. Data of peak pressure (PP), maximum force (MaxF-Newton), body weight corrected maximum force (BW_MaxF), contact area (CA-cm2) were analyzed for total foot and four plantar regions (hindfoot, midfoot, forefoot and toes). Results: Higher toes PP was found in the ages of 12–14 years in females compared to males (253.79 ± 104.93 vs 216.00 ± 81.12 for the age of 12, p = 0.011, 264.40 ± 65.02 vs 227.21 ± 83.4 for the age of 13, p = 0.044, 299.75 ± 140.60 vs 238.75 ± 103.32 for the age of 14, p = 0.005). Females' higher MaxF especially for toes (136.24 ± 48.54 vs 115.33 ± 46.03, p = 0.008) and smaller CA especially for forefoot (50.12 ± 5.79 vs 54.4893 ± 6.80, p = 0.001) were considerable in the late of early adolescence. Forefoot (305.66 ± 82.14 females p = 0.001, 281.35 ± 79.59 males p < 0.001) and total foot PP (374.08 ± 113.93 females, p = 0.035, 338.61 ± 85.85 males p = 0.009) at the age of 14 was significantly higher than in younger ages in both gender groups. Conclusion: The results indicate that especially the age of 14 years in early adolescence is a critical age for alteration in plantar pressure distribution. Interestingly females tended to increase their toe and forefoot plantar pressures compared to males by increasing age. We suggest that gender and age impact on toes plantar pressure alterations in early adolescence may be a possible risk factor for further foot impairments. Level of Evidence: Level III, Diagnostic Study. Keywords: Adolescent, Age, Gender, Plantar pressure, Pedobarography